Attitude control of LTA platform for generation of a non-oscillatory solar power. (1st September 2019) - Gupta, Sowmya; Duttagupta, Siddhartha P.; Vachhani, Leena; Mitra, Mira
Graphical abstract: Highlights: Dynamic stability analysis of Solar Powered Lighter Than Air Platform is presented. Solar response obtained by utilizing the orientation data of the airborne system. Single & tri tether optimal control for generation of non-oscillatory solar power. Wind-induced attitude destabilization to reduce power fluctuations by 71%. A preliminary experimental study on a discretized mechanical platform is given. Abstract: The applicability of solar energy depends either on the utilization of most efficient PV panels or on the experimental precision achieved while utilizing the existing highest efficient PV panels during implementation. Interestingly, in the present scenario, Solar Powered Lighter Than Air Platforms have been proved suitable for wide applications in defense and civil areas. Geographical mapping of the earth's surface and aerial surveillance can be performed by onboard sensors with long endurance and reliability. The airborne solar power may be affected by external wind disturbances causing oscillations in the aerial platform. In the present research, an emphasis has been laid on finding the impact of wind disturbance on the airborne solar power and later rectifying it by designing a suitable optimal controller in the feedback path of the system. The designed controller stabilizes the platform in a reasonably small time as compared to the uncontrolled system, resulting in the generation of a non-oscillatory solar power. The wind-induced attitude destabilization and subsequently the incurring power fluctuations in the harvested solar energy have been reduced by a factor of 3.46 in the closed loop system. The novelty of the work lies in implementing a tuned optimal controller for an effective orientation control with an application to harvest solar energy using Photo-Voltaic (PV) modules integrated on airborne platforms. The harvested solar energy with significantly reduced power oscillations can be used in many crucial applications against the unregulated oscillatory solar power.